PEMANFAATAN WEBSITE EDUKATIF DENGAN PEMBELAJARAN ARIAS PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN - Sasmito, Yusuf Anggar; Susilowati, Sri Mulyani Endang; Sukaesih, Sri (Journal of Biology Education, 2014)
Â  Abstract _______________________________________________________________ This study aimed to describe the effectiveness of utilization of educational websites with learning ARIAS on material structure and function of plant tissue on activity and learning outcomes of students in class XI SMA Negeri 8 Semarang. Â This study is optimal if students activity and their outcome in learning process showed â¥ 75% of students are active and very active with their outcome reached â¥ 75. This study is performed in SMA Negeri 8 Semarang in XI IPA 3 and XI IPA 4 class at second semester academic year 2013/2014. This study design is true experiment: pre-test post-test control group design. The datas of this study include student learning outcomes and their activities as main datas, and student responses, teacher response, and teacher performance as supporting data. The results of this study are learning completeness of experiment class is 76,67% while control class is 26,67%, and the Â N-gain value of test results tn pretest-posttest experimental class and control class obtained t = 3.3 and t = 2.0 tables with Î± = 5% to 3.3> 2.0 then Ho is rejected and Ha accepted, as well as student activities that are classified very active and active in experiment class is 76,67% while control class is 53,33%. The conclusion of this study is the utilization educative website and ARIAS model can optimize activity and learning outcomes of SMA Negeri 8 Semarang students in structure and function of plant tissue. Abstrak_______________________________________________________________Penelitian ini bertujuan untuk mendiskripsikan keefektifan pemanfaatanÂ websiteedukatif dengan pembelajaran ARIAS pada materi struktur dan fungsi jaringan tumbuhan terhadap aktivitas dan hasil belajar siswa kelas XI SMA Negeri 8 Semarang. Penelitian ini dikatakan optimal apabila aktivitas dan hasil belajar siswa dalamÂ  proses pembelajaran menunjukkanÂ  â¥ 75% siswa aktif dan sangat aktif, dengan hasil belajar mencapai â¥ 75. Penelitian ini dilakukan di SMA Negeri 8 SemarangÂ  pada kelas XI IPA 3 dan XI IPA 4 semester gasal tahun ajaran 2013/2014. Desain penelitian ini adalahÂ true experiment: pretest-posttest control group design. Data penelitian ini meliputi hasil belajar dan aktivitas sebagai data utama serta tanggapan siswa, tanggapan guru, dan kinerja guru sebagai data pendukung. Hasil penelitian ini adalah ketuntasan belajar pada kelas eksperimen sebesar 76,67% sedangkan kelas kontrol sebesar 26,67% dan hasil uji t N-gain nilaiÂ pretest posttest kelas eksperimen dan kelas kontrol diperoleh t hitung = 3,3 dan t tabel = 2,0 dengan Î±= 5% sehingga 3,3 > 2,0 maka Ho ditolak dan Ha diterima, serta aktivitas belajar siswa yang tergolong sangat aktif dan aktif pada kelas eksperimen sebesarÂ  76,67% dan kelas kontrol sebesar 53,33%. Dapat disimpulkan bahwa pemanfaatanÂ website edukatif dan model ARIAS dapat mengoptimalkan aktivitas danÂ  hasil belajar siswa keas XI SMA Negeri 8 Semarang pada materi struktur dan fungsi jaringan tumbuhan.Â